Perspektywy rolnictwa ekologicznego w Polsce w aspekcie integracji z Unią Europejską - Tańska-Hus, Bożena; Orlewski, Marcin (Prospects of Ecological Agriculture in Poland in Aspect of the Integration with the EU, 2005)
Before the accession of Poland the ecological agriculture appeared modestly against a background of the EU. Presently Poland as a member of EU realizes the rural - environmental programs which the means on the ecological agriculture comes from. These programs should render positive influence on the development of the ecological agriculture. Sale of ecological products became one of the greatest chance of Polish agriculture entering the European Union.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 360-364